PROBLEMATIKA SISWA SMK NURUL HUDA KAPONGAN DALAM PELAKSANAAN PEMBELAJARAN DARING (ONLINE) SELAMA MASA PANDEMI COVID-19 - Bayu Tirta Nugraha; Dassucik Dassucik; Tri Astindari (PENDIDIKAN SAINS DAN TEKNOLOGI, 2021)
The objectives to be achieved in this study are 1) To find out the implementation of online learning at SMK Nurul Huda Kapongan, Situbondo Regency for the 2020/2021 academic year. 2) To find out the problems or problems of online learning for students of SMK Nurul Huda Kapongan, Situbondo Regency for the 2020/2021 Academic Year. 3) To find out the efforts or solutions made to solve online learning problems at SMK Nurul Huda Kapongan, Situbondo Regency for the 2020/2021 Academic Year. This study uses a descriptive qualitative approach. The technique used in this research is the technique of observation, interview, and documentation. Data analysis in this study includes data reduction, data presentation, and drawing conclusions. Checking the validity of the data using triangulation of data sources and triangulation of methods. The results of this study conclude that (1) the implementation of online learning runs shorter, ie from 07:00 to 11:00 where there are two to three subjects every day; (2) In the online learning process students experience problems or obstacles, firstly the problem of quotas and internet networks, secondly some students do not have smartphones, thirdly the amount of material provided by the teacher, fourthly the lack of practicum, fifthly the lack of cooperation between parents and students, the six limitations of facilities and infrastructure. infrastructure; (3) The solution to solving problems experienced by students during online learning at SMK Nurul Huda Kapongan, Situbondo Regency is first, instructing students to study together at the location of the closest friends but not more than 3 people to overcome quota problems, internet networks and do not have smartphones, both teachers must evaluate and make learning more interesting so that students do not get bored quickly and are not too burdened with assignments, thirdly it is better for the school to facilitate students to be able to practice at face-to-face meetings, the four schools must establish good communication with people parents or guardians of students so that students become enthusiastic and motivated to learn, the five city governments can help so that institutions belonging to the remote village category can provide good internet access as well as a larger internet quota to support smooth online learning.